Poly (amido amine) dendrimer based membranes for wastewater treatment – A critical review - Ahmed T. Yasir (17302753) (2023)
Membrane based wastewater treatment technologies in which polymeric membranes are most commonly used have been extensively applied in water/wastewater treatment to help address the issue of water shortage through water/wastewater reclamation and reuse. However, polymeric membranes due to their hydrophobic nature are subject damage caused by accumulation of organic/inorganic fouling during filtration processes, which results in a number of issues such as low water flux and low pollutant rejection. Several strategies have been considered to address these challenges and effectively improve the membrane performances. Alteration of membrane properties strategy using suitable nanofillers such us poly (amido amine) or PAMAM has been largely studied. Herein, research efforts regarding the synthesis and properties of PAMAM along with the synthesis of PAMAM multifunctional nanocomposites were concisely reviewed for the first time. Membrane performance enhancement by incorporation of PAMAM were reviewed and discussed. Results and contributions achieved in the improvement of PAMAM incorporated membranes for the treatment of different types of wastewaters has been reviewed and summarized. Furthermore, perspectives on the current challenges and future research needs in the development and application of PAMAM incorporated polymeric membranes to benefit from the potentials that offer these promising new membrane nanofiller were discussed. Other Information Published in: Chemical Engineering Science License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ces.2023.118665